Pentad Analisis Pada Film Legend Of The Guardians - Latifah Novitasari; Prayudi Prayudi; Agung Prabowo (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2015)
The research aims to analyze representation of heroism value in the Legend Of The Guardians: The Owls Of Ga’hoole movie by using dramatism theory as the main theory and pentad analysis as a method. The results showed that the representation of the heroism value in the Legend Of The Guardians: The Owls Of Ga’Hoole movie indicated by drawing the five elements pentad consist of, act always includes scenes battle to save his kingdom. Scene is indicated by the use low key lighting concept to give the impression of dramatic, suspenseful and gripping the battle scenes in the movie. Agent illustrated with heroic character, never give up, willing to sacrifice, to protect the weak and defend the truth which is represented through the character Soren, Digger, Twillight, Gylfie and the Guardians. Agency displayed using war and believe gizzard activity in achieving a specific goal, and the last purpose shown by figures eradicate evil creatures in order to save the oppressed and restore peace to the kingdom of owls are great Ga’Hoole tree.